2022
DOI: 10.3389/fmicb.2022.934786
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Flora-Derived Kynurenic Acid Protects Against Intestinal Damage Caused by Candida albicans Infection via Activation of Aryl Hydrocarbon Receptor

Abstract: Colonization of the intestinal tract by Candida albicans (C. albicans) can lead to invasive candidiasis. Therefore, a functional intestinal epithelial barrier is critical for protecting against invasive C. albicans infections. We collected fecal samples from patients with Candida albicans bloodstream infection and healthy people. Through intestinal flora 16sRNA sequencing and intestinal metabolomic analysis, we found that C. albicans infection resulted in a significant decrease in the expression of the metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Metabolites produced by the microbiota can interact with the host and improve gut integrity. For example, stimulation of GPR35 by KYNA, was shown to enhance mucosal repair and stimulate mucus secretion, which increases the integrity of the gut epithelial barrier [70, 71]. Thus, increasing microbial production of KYNA in the small intestine may indirectly increase colonization resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolites produced by the microbiota can interact with the host and improve gut integrity. For example, stimulation of GPR35 by KYNA, was shown to enhance mucosal repair and stimulate mucus secretion, which increases the integrity of the gut epithelial barrier [70, 71]. Thus, increasing microbial production of KYNA in the small intestine may indirectly increase colonization resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Similar metabolic effects of KYNA injected intraperitoneally at a dose of 5 mg/kg/day, once a day for 1 to 4 weeks, to mice on a high-fat diet were described [ 93 ]. Very recently, it was reported that KYNA administered intraperitoneally three times decreased the colonization of the intestine by fungi and ameliorated intestinal injury, i.e., inhibited inflammation, promoted the expression of intestinal tight junction proteins, and protected from intestinal barrier damage caused by invasive Candida albicans infection in mice [ 94 ] ( Table 2 ). Other data indicating multiple health-promoting effects of KYNA come from studies in which the drug was acutely injected intraperitoneally ( Table S7 ).…”
Section: Kynurenic Acid Supplementationmentioning
confidence: 99%
“…The Hungarian group confirmed that KYNA protects against LPS-induced sepsis in subsequent publications, in which a much lower KYNA dose of 30 mg/kg, i.p., was used [ 99 , 100 ]. Most recently, Wang et al (2022) demonstrated that intraperitoneally administered KYNA (5 mg/kg; three times at days 3, 6, and 9) reduced the mortality of mice infected with Candida albicans [ 94 ]. Hsieh et al (2011) reported that KYNA administered intravenously at doses ranging from 30–100 mg/kg attenuated multiorgan dysfunction in rats exposed to heatstroke [ 101 ].…”
Section: Kynurenic Acid Supplementationmentioning
confidence: 99%
See 1 more Smart Citation
“…AhR activation leads to maintenance of epithelial barrier integrity, preventing permeability dependent on junctional changes, but in dysbiosis, even under an astonishing quantity of AhR ligands, metabolites such as the kynurenic acid (KynA) have a protective effect on the intestinal epithelium via activating AhR [ 105 ]. Taddese et al [ 106 ] found that gut bacteria have the potential to modulate the expression of biotransformation pathways in colonic epithelial cells in an AhR-dependent manner.…”
Section: Pesticide-induced Dysbiosis May Be Associated With Ahr Signa...mentioning
confidence: 99%